Proposed use of adrenaline (epinephrine) in anaphylaxis and related conditions: a study of senior house officers starting accident and emergency posts. Issue 921 (1st July 2002) - Gompels, L L; Bethune, C; Johnston, S L; Gompels, M M
Abstract : Senior house officers (SHOs) (n=78) at the start of their accident and emergency (A&E) post were given an anonymous five case history questionnaire, containing one case of true anaphylaxis, and asked to complete the medication they would prescribe. In the case of anaphylaxis, 100% would administer adrenaline (epinephrine) but 55% would do so by the incorrect route. In the remaining cases, 10%–56% would be prepared to administer adrenaline inappropriately. Only 5% were able to indicate the correct route and dose of adrenaline according to Resuscitation Council guidelines (UK). This has implications for training as the survey took place before the start of the A&E posting. Anaphylaxis is over-diagnosed and poorly treated despite Resuscitation Council guidelines.